2017
DOI: 10.3892/etm.2017.4419
|View full text |Cite
|
Sign up to set email alerts
|

Application of vibration response imaging technology in patients with community-acquired pneumonia before and after the treatment

Abstract: The value of vibration response imaging (VRI) technology in patients with community-acquired pneumonia (CAP) was assessed. The VRI images of 62 cases of CAP patients with normal lung functions before and after treatment were observed and the changes in images before and after treatment were compared. The maximum vibration energy value of CAP patients was 1.64±0.32, patients with unsmoothed vibration energy curve accounted for 88.71%, 41 cases (66.12%) had unordered dynamic images, 56 cases (90.32%) jumping ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It is mainly used to obtain the 3D coordinates of the external surface of the object and the 3D digital model of the object. It is not only fast, but also high precision, and can perfectly copy any object in the real world, To reproduce the real world in a digital form [11][12].…”
Section: ) Hardware Equipment Compositionmentioning
confidence: 99%
“…It is mainly used to obtain the 3D coordinates of the external surface of the object and the 3D digital model of the object. It is not only fast, but also high precision, and can perfectly copy any object in the real world, To reproduce the real world in a digital form [11][12].…”
Section: ) Hardware Equipment Compositionmentioning
confidence: 99%
“…These fifteen studies from Table 2 were conducted on patients with obstructed airways relating to respiratory diseases and were cross-sectional studies. Five studies [28][29][30][31][32] focused on patients with CRD, while six studies [33][34][35][36][37][38] reported on patients with lung consolidation, and the remaining four studies [39][40][41][42] inves-…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies [28][29][30][31][32] focused on patients with CRD, while six studies [33][34][35][36][37][38] reported on patients with lung consolidation, and the remaining four studies [39][40][41][42] investigated on COVID-19 patients. Eight studies [28,32,33,35,[39][40][41][42] utilized lung ultrasound (LUS), and the remaining seven studies [29][30][31]34,[36][37][38] utilized vibration response imaging (VRI) technology as observed in Table 2. The total number of participants per study ranged between ten and two hundred and nineteen.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VR technology has many applications in modern medicine. Duan YY introduced the application of VR technology in disaster medicine, 9 Jiang H, Chen J, and Cao J evaluated the value of vibration response imaging (VRI) technology in patients with community‐acquired pneumonia (CAP), 10 Ivan Molnár discussed the use of 3D digitalization and additive manufacturing technology in the medical field; 11 Hamacher A reviewed the extent to which VR technology has affected certain aspects of medicine, the applications currently being used in urology, and the expected future development trends 12 . From the above studies, it can be seen that the application of 3D VR technology in various fields of society is extremely broad, which further proves the great role and contribution of VR technology.…”
Section: Introductionmentioning
confidence: 99%